Profile of Endometrial Cancer Patients in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia - Alim, Kenny Dion; Tjokroprawiro, Brahmana Askandar; Kusumastuti, Etty Hary (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2023)
Highlights:1. Endometrial cancer is one of the most common cancers that affect the female genitalia.2. Endometrial cancer patients are mostly women in the age group of 51-60 years old, nullipara, with normal BMI, had type 1 endometrial cancer, and on stage II. AbstractIntroduction: Endometrial cancer is one of the most common cancers that affect the female genitalia. This study aimed to find the profile of endometrial cancer patients in Dr. Soetomo General Academic Hospital, Surabaya, from January 2019 to December 2020. Methods: Data were collected from medical records of endometrial cancer patients in Dr. Soetomo General Academic Hospital, Surabaya, from January 2019 to December 2020. There were 154 endometrial cancer patients, and 66 met the inclusion and exclusion criteria. Forty-one of those patients also had curettage grades. Data were extracted from the medical records of those patients.Results: There were 66 samples used in this study. The most common age group of patients was the age group of 51-60 years old (40.91%). The highest parity rate was nullipara (28.79%). The highest body mass index (BMI) group was the normal BMI group (42.42%). The most common type of endometrial cancer was type 1, with endometrioid adenocarcinoma (93.94%). The most common stage of endometrial cancer was stage II (36.36%). The similarity between curettage and post-operative grade was 70.73%. Patients with a history of diabetes mellitus were 6.06%, and patients with a history of hypertension were 12.12%.Conclusion: Most of the endometrial cancer patients in Dr. Soetomo General Academic Hospital, Surabaya, were women in the age group of 51-60 years old, nullipara, with normal BMI, had type 1 endometrial cancer, and on stage II. Most patients had similar curettage and post-operative grades, and only a minority had diabetes mellitus and hypertension histories.